Experimental and numerical studies on a composite MR damper considering magnetic saturation effect. (1st February 2017) - Zhang, Xiangcheng; Zhang, Xu; Zhao, Yixiao; Zhao, Jun; Xu, Zhaodong
Highlights: We test the composite magnetorheological damper under different loading conditions. The damper force won't increase after the magnetic saturation occurs. Magnetic saturation occurs when electric current value is greater than 1.8 amperes. We propose a modified Sigmoid model to describe the behavior of the CMR damper. Abstract: In this paper, a composite magnetorheological (CMR) damper was experimented under different electric currents, displacement amplitudes and frequencies to investigate its nonlinear hysteretic behavior, magnetic saturation property, energy dissipation capability and fatigue resistance performance. The modified Sigmoid model was proposed to describe the behaviors of the CMR damper, and the predictions obtained from the proposed model were validated using the data collected from the experiments, comparisons between predictions by Bingham model, Bouc-Wen model, and the modified Sigmoid model and test results were carried out. It was found that the proposed model can describe the effects of electric current, displacement and frequency on the nonlinear hysteretic behavior and magnetic saturation property of the CMR damper.